Relationship between anatomical variations in the aortic arch and risk of aneurysm formation ‒ a systematic review - Jain, Sanjeev Kumar; Sharma, Sonika (European Journal of Clinical and Experimental Medicine, 2026)
Introduction and aim. Anatomical variation in the aortic arch has been proposed as an aneurysm risk factor based on changed hemodynamic forces and structural stress in arterial walls. Knowledge of these variations will be valuable in optimizing surgical planning and management of risks for patients to undergo cardiovascular and thoracic procedures. This systematic review summarized existing literature to assess the relation of different variations in the aortic arch with the risk of aneurysm formation by consolidating evidence of clinical relevance and predictive markers of risk. Material and methods. We conducted our searches in seven databases: PubMed, Embase, Scopus, Web of Science, Cochrane Library, CINAHL, and ProQuest, using Boolean operators and MeSH terms. The ROBINS-I tool was used to assess the risk of bias in studies, including confounding, participant selection, and outcome reporting. GRADE was used to evaluate global certainty of evidence, which also considered consistency, directness, and precision of evidence. Studies were eligible based on strict eligibility criteria and reported findings on specific aortic arch and their potential association with aneurysm formation. Results. The review included 12 studies that varied in terms of sample size and used a mostly retrospective design. According to the findings evaluated, certain forms of the aortic arch, for example, the bovine arch and aberrant right subclavian artery, posed an increased risk of developing proximal versus distal aneurysms. Advanced imaging studies, such as 4D flow MRI and enhanced CT, aided in the selection of at-risk patients, as they described the flow pressure dynamics with detailed assessments. While several authors reported consistent associations of anatomical variation with risk, other authors found no significant correlation and thus suggested variability in clinical relevance. The general review showed both converging and divergent findings of the review about the predictive value of certain types of arch for aneurysm risk. Conclusion. This systematic review highlights the incorporation of knowledge on aortic arch variation as part of the detailed risk assessment required in aneurysmal formation among patients. Although some forms, such as the bovine arch and the aberrant right subclavian artery, did indeed demonstrate the potential to be predictive of complications, study inconsistencies provide reason for continuing research on the topic. Advanced imaging may improve medical decision-making, as patient risk stratification would be feasible with greater information on anatomical variation.